Paleoseismology - McCalpin, James (International geophysics series, 1996)
This is the first book in the English language to be devoted solely to paleoseismology. It summarizes the development of the field from the 1960s to the present, encompassing material that is currently widely dispersed in journal articles. The ten chapters included in this text span the entire range of techniques currently used in paleoseismic reconstruction, and are contributed by active practitioners at the forefront of paleoseismic research. Includes comprehensive review of techniques currently used in paleoseismology Emphasizes practical methods of data collection, and field studies Covers interpretation of field data based on current theory concerning fault segmentation and recurrence cycles Contains more than 170 line drawings and 50 photographs of paleoseismic phenomena.